Impairment in the telocyte/CD34+ stromal cell network in human rheumatoid arthritis synovium. Issue 4 (21st December 2020) - Rosa, Irene; Faussone‐Pellegrini, Maria Simonetta; Romano, Eloisa; Ibba‐Manneschi, Lidia; Matucci‐Cerinic, Marco; Manetti, Mirko
Abstract: Telocytes (TCs)/CD34 + stromal cells have recently emerged as peculiar interstitial cells detectable in a variety of organs throughout the human body. TCs are typically arranged in networks establishing unique spatial relationships with neighbour cells and likely contributing to the maintenance of tissue homeostasis by both cell‐to‐cell contacts and releasing extracellular vesicles. Hence, TC defects are being increasingly reported in different pathologies, such as chronic inflammatory and fibrotic conditions. In this regard, TCs/CD34 + stromal cells have been shown to constitute an intricate interstitial network in the subintimal area of the normal human synovial membrane, but whether they are altered in chronic synovitis has yet to be explored. We therefore undertook a morphologic study to compare the distribution of TCs/CD34 + stromal cells between normal synovium and chronically inflamed synovium from patients with rheumatoid arthritis (RA) by using CD34 immunohistochemistry and CD31/CD34 double immunofluorescence. CD34 immunostaining revealed that, at variance with normal synovium, the inflamed and hyperplastic RA synovial tissue was nearly or even completely devoid of TCs/CD34 + stromal cells. Double immunofluorescence confirmed that almost all CD34 + tissue components detectable in RA synovium were blood vessels coexpressing CD31, while a widespread network of CD31 − /CD34 + TCs was clearly evident in the whole sublining layer of normal synovium. In the context of the emerging diverse roles of TCs/CD34 + stromal cells in the regulation of tissue homeostasis and structure, the remarkable impairment in their networks herein uncovered in RA synovium may suggest important pathophysiologic implications that will be worth investigating further.